The consequences of debris flows in Brazil: a historical analysis based on recorded events in the last 100 years - Cabral, Victor [UNESP]; Reis, Fábio [UNESP]; Veloso, Vinicius [UNESP]; Correa, Claudia [UNESP]; Kuhn, Caiubi [UNESP]; Zarfl, Christiane (Springer Nature, 2023)
This study aims at providing an overview of the socioeconomic consequences that debris-flow events have caused in Brazil, positioning the country in the international scenario and identifying areas where targeted actions are necessary. The analysis is conducted by calculating the debris-flow mortality rate (MR) and by using the so-called F-N plots (frequency of events that have caused N or more fatalities vs. the number of fatalities), based on a compilation of debris-flow-related disasters from 1920 to 2021. In total, 45 debris-flow events were documented in the considered period, responsible for 5771 fatalities and more than 5.5 billion USD in economic losses. The Serra do Mar Mountain Range is the main site of reported debris-flow occurrences (64.5%), followed by Serra da Mantiqueira (13.3%), and Serra Geral (13.3%). Southeast Brazil (SEB) is the region most affected by debris-flow events, due to the highest population density and the development of several cities in hilly areas, such as Petrópolis (Rio de Janeiro state) and Cubatão (São Paulo state). The debris-flow MR of SEB is higher than any other region in Brazil, pushing the national debris-flow MR upwards, and the F-N curve of SEB consolidates the region as the one with the highest risk to the phenomenon, indicating a higher probability of fatal events. The F-N plots further show that debris-flow events in Brazil represent a higher societal risk than in countries such as China, Japan and Italy. While there are differences in country size and the scale effect should be considered, these results highlight the urgent need for investments in disaster prevention and preparedness programs.
Keywords: Debris flows; F-N curve; Landslide database; Mortality rate; Natural disasters